DIGITAL TRANSFORMATION OF PROFESSIONAL TRAINING INSTITUTIONS USING AI TECHNOLOGIES (Eureka Journal of Education & Learning Technologies, 2026)
This study explores the role of artificial intelligence (AI) technologies in the digital transformation of professional training institutions. The rapid development of digital technologies has significantly changed modern educational systems, creating new opportunities for improving teaching methods, learning resources, and institutional management. The research focuses on how AI-based technologies can enhance the quality of professional education by providing personalized learning experiences, intelligent assessment systems, and automated educational support. The paper also examines the advantages of integrating AI into professional training institutions, including increased learning efficiency, improved student engagement, and the development of practical skills required in the modern labor market. Furthermore, the study highlights the challenges associated with implementing AI technologies, such as technical limitations, data privacy concerns, and the need for teacher training in digital competencies.
Keywords: Artificial intelligence, digital transformation, professional training institutions, educational technologies, AI-based learning, digital education, vocational training, innovative learning systems.